Nomination contests: theory and empirical evidence from professional soccer - Jeanine Miklós-Thal; Hannes Ullrich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper develops a theory of contests based on perceived abilities, and provides evidence for the predictions of this theory using panel data from professional soccer. We examine how soccer players perform in club matches during the informal)nomination contests for national teams prior to an important international Cup, the Euro 2008. Our differences-in-differences analysis uses players from nonqualified nations who play in the same league as a control group. We find a large positive effect of nomination contest participation on several output measures for players with intermediate chances of being nominated, as proxied by past national team participations. For players with no prior national team experience there is no significant effect. We also find support for the theory that players whose nomination is close to certain reduce their effort in order to avoid injuries or exhaustion prior to the Cup. Finally, any positive reaction is strongest for young players.
Keywords: I20; 330; Extensives Spiel; Erwerbsverlauf; Qualifikation; Wahrnehmung; Fußballsport; Professioneller Sport; Nationalstaat; Theorie; Deutschland